Improving early childhood development outcomes in times of COVID-19: Experimental evidence on parental networks and SMS messages - Juan Manuel Hernández-Agramonte; Olga Namen; Emma Näslund-Hadley; María Loreto Biehl (Inter-American Development Bank (IDB), 2022)
This paper describes a policy experiment implemented in Costa Rica to increase learning during the COVID-19 pandemic. The experiment provided parents of preschool students with text messages to support their children's learning at home. After 15 weeks of intervention, the cognitive skills of children whose parents received the text messages rose 0.11-0.12 standard deviations. An increase in parental involvement through the proposed activities drove the effect. No evidence was found that information is transferred within parental networks.
Keywords: C93; I21; J13; O15; 330; Education; Early Childhood Development; Text Messages; Parenting; COVID-19